1991
DOI: 10.1093/sleep/14.6.546
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Treatments for Positional Sleep Apnea

Abstract: Sixty male patients all with apnea plus hypopnea indices (A + HI) above 12.5, who met a criterion of positionality by having two or more times the rate of these events during supine sleep in comparison to their lateral sleep rate, were randomly assigned to one of four treatments for 8 weeks. All were restudied for two nights, one with and one without treatment devices. On treatment more than half the patients in each group reduced their A + HI to within normal limits and a third remained WNL without the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
2
7

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 0 publications
1
99
2
7
Order By: Relevance
“…Nevertheless, the consistency of the results is strikbeing an OSA positional patient correlates with the RDI, BMI and age in a general reverse relationship, of positional devices have also shown that many patients can successfully learn to avoid the supine ie, an OSA patient with a severe RDI and who is obese (BMI Ͼ30) and older than age 60 is signifiposition during sleep. 33,38,62 However, long term compliance data using these different techniques are cantly less likely to be positional than an OSA patient with a moderate RDI who is not obese and not yet available and studies investigating this issue are clearly needed. This is particularly the case who is less than 60 years of age.…”
Section: Bp Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the consistency of the results is strikbeing an OSA positional patient correlates with the RDI, BMI and age in a general reverse relationship, of positional devices have also shown that many patients can successfully learn to avoid the supine ie, an OSA patient with a severe RDI and who is obese (BMI Ͼ30) and older than age 60 is signifiposition during sleep. 33,38,62 However, long term compliance data using these different techniques are cantly less likely to be positional than an OSA patient with a moderate RDI who is not obese and not yet available and studies investigating this issue are clearly needed. This is particularly the case who is less than 60 years of age.…”
Section: Bp Variabilitymentioning
confidence: 99%
“…The patients arrived at the sleep unit around turbances to a great extent and in some cases even 20.00 and the PSG recordings usually began entirely. 33,38 between 22.00 and midnight. The aim of this study is to assess the effect of avo-…”
Section: Introductionmentioning
confidence: 99%
“…Arrhythmias need proper ECG monitoring, and a separate 24h Holter monitor may be more appropriate. Posture needs to be measured owing to the exquisite sensitivity of OSA to the supine posture, and the response of OSA to posture training when this is the case (Cartwright 1984;Cartwright et al 1991). 'Moderate' sleep apnoea is usually due to individuals with supine-only obstructions who spend variable proportions of their sleep time on the back.…”
Section: Eog Onlymentioning
confidence: 99%
“…8 Other common therapeutic options have included surgical intervention of the upper airway, weight loss, the use of oral appliances, and when indicated, positional therapy. [9][10][11][12][13] More recently, data have identified that positional OSA, where sleep-disordered breathing events occur predominantly in the supine position, is quite prevalent in patients with mild and moderate OSA.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] These studies have included those utilizing training methods [9][10] or devices designed to prevent the patients from rolling on their back. positional OSA.…”
mentioning
confidence: 99%